Cool hand Luke - Newman, Paul, 1925-2008.; Kennedy, George, 1925-; Martin, Strother, d. 1980.; Rosenberg, Stuart, 1925-; Jalem Productions (Burbank, Calif. : Warner Home Video, 1997)
Part of a chain gang, Luke is the loner who won't or can't conform to the arbitrary rules of his captivity. Man's inhumanity to man in the person of the Captain takes Luke to the limits of physical and psychological endurance. Tragic drama with some comic elements.
Includes theatrical trailer.
Original production: c1967.
Screenplay by Donn Pearce and Frank R. Pierson adapted from the novel by Donn Pearce ; director of photography, Conrad Hall ; music by Lalo Schifrin.
Paul Newman, George Kennedy, Strother Martin ... [et al.].
DVD.
In English; dubbed also into French or Spanish with optional subtitles in English, French or Spanish.
Closed-captioned.
Keywords: Convict labor -- Drama; Prisoners -- United States -- Drama; Video recordings for the hearing impaired; Feature films